Accidental injury, self‐injury, and assault among children of women with schizophrenia: a population‐based cohort study. (11th February 2021) - Taylor, Clare L.; Brown, Hilary K.; Saunders, Natasha R.; Barker, Lucy C.; Chen, Simon; Cohen, Eyal; Dennis, Cindy‐Lee; Ray, Joel G.; Vigod, Simone N.
Abstract: Objective: We aimed to compare the risk for injury overall and by intent (accidental injury, self‐injury, and assault) among children born to women with versus without schizophrenia. Methods: Using health administrative data from Ontario, Canada, children born from 2003 to 2017 to mothers with ( n = 3769) and without ( n = 1, 830, 054) schizophrenia diagnosed prior to their birth were compared on their risk for child injury, captured via emergency department, hospitalization, and vital statistics databases up to age 15 years. Cox proportional hazard models generated hazard ratios for time to first injury event (overall and by intent), adjusted for potential confounders (aHR). We stratified by child sex and age at follow‐up: 0–1 (infancy), 2–5 (pre‐school), 6–9 (primary school), and 10–15 (early adolescence) planning to collapse age categories as needed to obtain stable and reportable estimates. Results: Maternal schizophrenia was associated with elevated risk for child injury overall (105.4 vs. 89.4/1000 person‐years (py), aHR 1.08, 95% CI 1.03–1.14), accidental injury (104.7 vs. 88.1/1000py, 1.08, 1.03–1.14), for self‐injury (0.4 vs. 0.2/1000py, 2.14 1.18–3.85), and assault (1.0 vs. 0.3/1000py, 2.29, 1.45–3.62). By child sex, point estimates were of similar magnitude and direction, though not all remained statistically significant. For accidental injury and self‐injury, the risk associated with maternal schizophrenia was most elevated in 10–15‐year‐olds. For assault, the risk associated with maternal schizophrenia was most elevated among children in the 0–1 and 2–5‐year‐old age groups. Conclusion: The elevated risk of child injury associated with maternal schizophrenia, especially for self‐injury and assault, suggests that targeted monitoring and preventive interventions are warranted.